Magnetostratigraphic constraints on the age of the lower Beaufort Group, western Karoo basin, South Africa, and a critical analysis of existing U‐Pb geochronological data. (27th October 2015) - Tohver, E.; Lanci, L.; Wilson, A.; Hansma, J.; Flint, S.
Abstract: We studied three partially overlapping sections with a composite thickness of ∼600 m in the upper Permian fluvial siltstones and fine‐grained sandstones of the Abrahamskraal Formation, the basal unit of the Beaufort Group, in the Karoo Basin of Western Cape Province, South Africa. Paleomagnetic analysis reveals three components of Natural Remanent Magnetization (NRM). Heating to ∼180°C removes a remanent magnetization parallel to the present‐day field, which is interpreted as a viscous overprint. An intermediate unblocking temperature component is removed by heating to 450°C; this direction is always of normal polarity and is identical to a regional overprint imparted during the Early Jurassic emplacement of the Karoo Large Igneous Province. A high‐temperature component isolated above 450°C is of dual polarity and is interpreted as primary on the basis of a positive reversals test. The virtual geomagnetic pole position for the Abrahamskraal Formation computed from the average high‐temperature characteristic remanent magnetization direction is in agreement with the late Permian directions for stable Gondwana and with previous results from the lowermost Abrahamskraal Formation and Waterford Formation at the Ouberg Pass section. The predominantly normal polarity of this magnetization is in agreement with either a middle‐late Lopingian age (ca. 254–256 Ma) or a late Guadalupian age (ca. 262 Ma) according to the global geomagnetic polarity time scale. We integrate these new results with existing magnetostratigraphic, biostratigraphic, and geochronological results from the Karoo Basin, with particular emphasis on the controversy over zircon age data reported from the underlying Ecca Group. Key Points: Primary magnetizations are preserved in the lower Beaufort Group in the Karoo Basin The magnetostratigraphy is compatible with a late Permian age for the Beaufort Group A re‐examination of existing data from the underlying Ecca Group indicates a mid‐Permian age